Pengaruh Sistem Pengendalian Intern dan Komitmen Organisasi terhadap Kualitas Laporan Keuangan Pemerintah Daerah dengan Kompetensi Sumber Daya Manusia sebagai Variabel Moderating - Widatul Aziyah; Heri Yanto (Politeknik Ganesha Medan, 2022)
This study aims to examine the effect of the internal control system and organizational commitment on the quality of local government financial reports. The population and sample in this study used are State Civil Apparatus who work in the finance department in the OPD of Batang Regency, amounting to 88 people. Sampling was used using the purposive sampling technique. The data used is primary data in the form of a questionnaire. The data analysis used is descriptive, classical assumption test, absolute value difference test, coefficient of determination test, F test, and T-test with the help of IBM SPSS software version 25.0. This study results that there is a significant positive effect between the internal control system on the quality of local government financial reports. Organizational commitment does not effect the quality of local government financial reports. Meanwhile, the competence of human resources is not able to moderate the influence between the internal control system and organizational commitment on the quality of local government financial reports. It is recommended that further research be added to the research sample, namely the accounting department, and it is hoped that the next researcher can use moderating variables to retest the hypothesis that has no effect.